2003
DOI: 10.1046/j.1464-410x.2003.04316.x
|View full text |Cite
|
Sign up to set email alerts
|

Serenoa repens extract for benign prostate hyperplasia: a randomized controlled trial

Abstract: OBJECTIVE To compare the effect of a Serenoa repens extract with placebo for symptoms of benign prostatic hyperplasia (BPH). PATIENTS AND METHODS In a double‐blind placebo‐controlled randomized trial between January 1999 and March 2000, 100 men with symptoms of BPH, aged < 80 years, with a maximum urinary flow rate of 5–15 mL/s for a voiding volume of 150 mL, were randomly and equally allocated to 320 mg S. repens extract or placebo (paraffin oil). The main outcome measures were the International Prostate Symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 20 publications
1
62
1
6
Order By: Relevance
“…The overall number of 100 patients was planned. The aim was to find the clinically relevant differences between the treatment groups with changes from the baseline on the total IPSS score of at least 5.6, as previously planned by Willetts et al [7] in a placebo-controlled study on a saw palmetto herbal blend for men with LUTS/BPH.…”
Section: Methodsmentioning
confidence: 99%
“…The overall number of 100 patients was planned. The aim was to find the clinically relevant differences between the treatment groups with changes from the baseline on the total IPSS score of at least 5.6, as previously planned by Willetts et al [7] in a placebo-controlled study on a saw palmetto herbal blend for men with LUTS/BPH.…”
Section: Methodsmentioning
confidence: 99%
“…The best described and studied phytotherapeutic agent, Serenoa repens (saw palmetto), has shown mild to moderate efficacy in reducing nocturia, increasing maximal urinary flow and improving International Prostate Symptom Score (IPSS) in men with BPH, 40,41 with results comparable with that of tamsolusin. 40,42,43 However, other trials have shown no significant beneficial effect of S. repens compared with placebo, 44 and a recent Cochrane Review concluded that S. repens was not more effective than placebo for the treatment of urinary symptoms consistent with BPH. 45 Pygeum africanum, an extract from the African prune tree, is another popular alternative remedy for BPH, 46 and has been shown in a Cochrane review to provide moderate relief from the urinary problems caused by BPH.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Many of the existing papers cover only a short-term follow up of 16 months [Willetts et al 2003;Descotes et al 1995]. More recently, a few studies included a longterm follow up [Pytel et al 2002].…”
Section: Treatment Of Lower Urinary Tract Symptomsmentioning
confidence: 99%